Amelioration in the quality traits of forage pearl millet (Pennisetum glaucum) by application of liquid microbial inoculants - GULAB, PANDOVE; VIDHI, ARORA; HARPREET, OBEROI (The Indian Journal of Animal Sciences, 2022)
Pearl millet (Pennisetum glaucum) is a promising dual purpose (fodder and grain) crop. The present investigation was carried to evaluate the effect of liquid microbial inoculants on the quality traits of forage pearl millet. Experiment was laid out in randomized complete block design with a total of 12 treatment combinations of liquid microbial inoculants (Azotobacter sp., Sphingobacterium sp., Stenotrophomonas maltophilia and Burkholderia seminalis) with 100% Recommended Dose of Fertiliser (RDF) and replicated thrice. The application of the liquid microbial inoculants showed improvement in the quality traits over the uninoculated control at both the locations. The treatment T9 (RDF + B. seminalis + S. maltophilia) showed significant increase in the total sugars, ash content, CP (crude protein) and IVDMD (in vitro dry matter digestibility), while significant decrease in the ADF (acid detergent fibre) and NDF (neutral detergent fibre). Further, very strong positive and significant correlation was observed between ADF, NDF and the various antinutrients while they were recorded to be negatively correlated with rest of the quality parameters. Therefore, it can be concluded that liquid microbial inoculants could play a predominant role in improving the forage quality of forage pearl millet